Keberlanjutan Komunitas Seni Kriya Melalui Pariwisata Berbasis Masyarakat di Desa Wisata Kedung Gede Jakarta Selatan - Gagih Pradini; Anisa Putri Kusumaningrum; Vironika Agustin Saputra; Putri Aulia Ardani; Dipa Teruna (Jurnal Ilmiah Wahana Pendidikan, 2023)
It cannot be denied that tourism is one of the largest and fastest growing industries in the world. However, in its development tourism has also experienced many challenges. This is what then triggers the emergence of various forms of alternative tourism, one of which is community-based tourism. The tourist village of Kedung Gede, South Jakarta is one of the tourist villages that implements community-based tourism. One of the main attractions of the Kedung Gede Tourism Village is the craft arts which are well looked after by the local community. The existence of this craft art is the main attraction for tourists who come to visit this village, where they have the unique opportunity to participate directly in craft art making activities.